2021
DOI: 10.3389/fimmu.2021.655122
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Efficient Genome Editing of Human FOXP3+ Regulatory T Cells

Abstract: FOXP3+ regulatory T cells (Tregs) are central for maintaining peripheral tolerance and immune homeostasis. Because of their immunosuppressive characteristics, Tregs are a potential therapeutic target in various diseases such as autoimmunity, transplantation and infectious diseases like COVID-19. Numerous studies are currently exploring the potential of adoptive Treg therapy in different disease settings and novel genome editing techniques like CRISPR/Cas will likely widen possibilities to strengthen its effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 75 publications
(118 reference statements)
0
13
0
Order By: Relevance
“…Indeed, literature has shown IL-6R expression on human Tregs as well [43], which renders Tregs, and more specifically thymic Tregs [44], more susceptible to Th17 skewing [45,46]. Previous reports showed that IL-1 and IL-6 alone and together downregulate FOXP3 while inducing IL-17 expression on Tregs in a STAT3-dependent way [33,[47][48][49][50][51], also in EAE and rheumatoid arthritis [26,29,52]. As these cytokines are not BBB specific, these effects will not be limited to MS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, literature has shown IL-6R expression on human Tregs as well [43], which renders Tregs, and more specifically thymic Tregs [44], more susceptible to Th17 skewing [45,46]. Previous reports showed that IL-1 and IL-6 alone and together downregulate FOXP3 while inducing IL-17 expression on Tregs in a STAT3-dependent way [33,[47][48][49][50][51], also in EAE and rheumatoid arthritis [26,29,52]. As these cytokines are not BBB specific, these effects will not be limited to MS.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in IL2RA expression may affect immune and inflammatory signaling cascade responses, which in turn affect CD4 + T cell differentiation and TReg cell suppressive activity (Asouri et al, 2020). IL2 signaling is involved in the differentiation and homeostasis of regulatory T cells (Tregs), and IL2 signaling is involved in the induction of cell growth and effector T cell proliferation (Zeebroeck et al, 2021). Pre-activation of IL-12, IL-15, and IL-18 was shown to upregulate IL2RA (CD25) expression (Akman et al, 2021).…”
Section: Phaseol May Reduce Inflammatory Cell Activation and Inflamma...mentioning
confidence: 99%
“…IL-2RA deletion resulted in the loss of STAT5 signaling and Treg suppressive function. Similarly, IL-6R alpha subunit showed reduction in STAT3 activation, suggesting the possibility of genetically engineered Tregs to be resistant to IL-6 mediated Treg instability (88). While transcriptional regulation is not a focus of this review, a paper by Schumann et al entitled "functional CRISPR dissection of gene networks controlling human regulatory T cell identity" pressured Tregs under inflammatory cytokines while using CRISPR/Cas9 to reveal important transcription factors regulating Treg instability in the inflammatory settings.…”
Section: Foxp3 Stability Through Functional and Phenotypic Screensmentioning
confidence: 99%
“…IL-2RA deletion resulted in the loss of STAT5 signaling and Treg suppressive function. Similarly, IL-6R alpha subunit showed reduction in STAT3 activation, suggesting the possibility of genetically engineered Tregs to be resistant to IL-6 mediated Treg instability ( 88 ). While transcriptional regulation is not a focus of this review, a paper by Schumann et al.…”
Section: Foxp3 Stability Through Functional and Phenotypic Screensmentioning
confidence: 99%